2013
DOI: 10.1016/j.eplepsyres.2013.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of scalp-fast oscillations among patients with different spiking rate and their role as epileptogenicity marker

Abstract: SummaryIntroduction-We aim to analyze the fast oscillations in the scalp EEG of focal epilepsy patients with low-to-high rates of interictal epileptiform discharges (IEDs), in order to determine how this neurophysiological feature influences fast oscillation occurrence and their significance as markers of the seizure onset zone (SOZ).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
87
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(94 citation statements)
references
References 22 publications
6
87
1
Order By: Relevance
“…However, recent work has detected spontaneous ripple-frequency HFOs associated with spikes in scalp EEG from children with continuous spike and wave during slow wave sleep [115]. Two subsequent studies detected gamma-and ripple-frequency HFOs in the scalp EEG of adults with epilepsy [116,117]. In these studies, HFOs were often associated with IIS, but some occurred independently of IIS, and rates of HFO and IIS were higher inside than outside the SOZ.…”
Section: Interictal Hfosmentioning
confidence: 99%
“…However, recent work has detected spontaneous ripple-frequency HFOs associated with spikes in scalp EEG from children with continuous spike and wave during slow wave sleep [115]. Two subsequent studies detected gamma-and ripple-frequency HFOs in the scalp EEG of adults with epilepsy [116,117]. In these studies, HFOs were often associated with IIS, but some occurred independently of IIS, and rates of HFO and IIS were higher inside than outside the SOZ.…”
Section: Interictal Hfosmentioning
confidence: 99%
“…A recent study showed that interictal surface ripples decrease after treatment with ACTH in children with West Syndrome (Kobayashi et al, 2015). Co-occurrence of ripples with epileptic spikes is reported in 44-64% of all ripples in intracranial and surface recordings (Melani et al, 2013;Andrade-Valenca et al, 2011;Urrestarazu et al, 2007;Jacobs et al, 2009;Wang et al, 2013). Ripples co-occurring with a spike are more related to the seizure onset zone than ripples without a spike (Wang et al, 2013).…”
Section: Introductionmentioning
confidence: 96%
“…This increases the population for whom HFO analysis is available, beyond the small group of drug-resistant focal epilepsy patients who are candidates for surgery with intracerebral electrodes. Reports describe 50-100 Hz activity in ictal recordings (Kobayashi et al, 2004(Kobayashi et al, , 2009, ripples in interictal EEG in adults with focal epilepsy (Andrade-Valenca et al, 2011;Melani et al, 2013;Zelmann et al, 2013), in children with continuous spike and wave in slow-wave sleep (Kobayashi et al, 2010), and idiopathic partial epilepsy (Kobayashi et al, 2011). A recent study showed that interictal surface ripples decrease after treatment with ACTH in children with West Syndrome (Kobayashi et al, 2015).…”
Section: Introductionmentioning
confidence: 96%
“…Then, interictal HFOs were identified in the scalp EEG of patients with focal epilepsy with higher rates inside the SOZ 28 . Interestingly, HFOs were more frequent in patients with high numbers of interictal epileptiform discharges (IEDs), and they were found to be more specific than IEDs for the SOZ 29 , highlighting the relation of HFOs with epileptogenicity.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study proposed that HFOs recorded non-invasively with scalp EEG represent the sum of activity of multiple spatially distributed focal and coherent sources 60 . So far, few studies 28,29,37,38,60 managed to show that HFOs can be detected non-invasively using scalp EEG and MEG; even fewer localized this activity by solving the inverse problem [37][38] .…”
Section: Significance Of the Technique With Respect To Existing/altermentioning
confidence: 99%